Assessment of gamma oryzanol variability, an attractive rice bran bioactive compound - Lageiro, Manuela (2018)
Gamma-oryzanol is a compound present on rice bran, which has been studied for its bioactive properties, including its cytotoxic activity. The gamma-oryzanol biosynthesis occurs on the lipidic membrane of the plant and can be influenced by edaphoclimatic grown conditions. Two Portuguese rice varieties (Ceres and Macarico) from 6 growing environments were analysed in order to explore the influence of the growing conditions on the gamma-oryzanol content, its constituents, and cytotoxic effect against 4 human tumour cell lines (NCI-H460, HeLa, HepG2, and MCF-7). The overall variability of gamma-oryzanol concentration was from 1.56 g/Kg to 3.19 g/Kg, Ceres reveals higher values than Macarico; those concentrations also varied with the growing environment. The environment was also determinant for the individual concentration of the 3 gamma-oryzanol compounds (cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, and campesteryl ferulate). A cytotoxic effect was observed for all the tested tumour cell lines and also varied with the growing environment.